2017
DOI: 10.3390/s18010036
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Comparison of Different Formats of Immunochromatographic Serodiagnostics

Abstract: In this study, a comparative theoretical and experimental analysis of two immuno-chromatographic serodiagnostics schemes, which differ in the immobilization of immunoreagents and the order of the formation of immune complexes, is performed. Based on the theoretical models, the assays are characterized to determine which scheme has a higher quantity of the detected complex and thus ensures the sensitivity of the analysis. The results show that for the effective detection of low-affinity antibodies, the scheme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…(Figure 1). Although the traditional LFIA schemes for antibody detection uses AuNPs conjugated with an immunoglobulinbinding protein and the pathogen's antigen immobilized in the analytical zone (test line), some studies have shown that a less conventional scheme using AuNPs directly conjugated with pathogen's antigen molecules for detection of serum antibodies can achieve greater diagnostic sensitivity (Sotnikov et al, 2015(Sotnikov et al, , 2018. This increase in sensitivity is achieved by targeting the capture of the antibodies of interest in the conjugation process, due to the specific interaction of those antibodies with the corresponding antigens present in the conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 1). Although the traditional LFIA schemes for antibody detection uses AuNPs conjugated with an immunoglobulinbinding protein and the pathogen's antigen immobilized in the analytical zone (test line), some studies have shown that a less conventional scheme using AuNPs directly conjugated with pathogen's antigen molecules for detection of serum antibodies can achieve greater diagnostic sensitivity (Sotnikov et al, 2015(Sotnikov et al, , 2018. This increase in sensitivity is achieved by targeting the capture of the antibodies of interest in the conjugation process, due to the specific interaction of those antibodies with the corresponding antigens present in the conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…In real samples, the concentration of specific antibodies against individual antigens rarely exceeds 2 µM, even in hyperimmune sera [ 36 ]. Therefore, a decrease in the color intensity to an undetectable limit is unlikely.…”
Section: Results and Discussion (Experimental)mentioning
confidence: 99%
“…To overcome this limitation, an alternative immunochromatographic serodiagnostics format has been proposed, in which the label is conjugated to the antigen, and an immunoglobulin-binding protein is sorbed in the analytical zone [ 32 , 33 , 34 , 35 , 36 , 37 ]. This approach prevents the inclusion of the label in complexes with nonspecific immunoglobulins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking immunoglobulin-binding sites on the surface of the label by nonspecific immunoglobulins leads to a reduction in the signal, which in turn makes it difficult to interpret the results of the assay accurately [20]. Therefore, an increase in sensitivity is most in demand for immunochromatographic serodiagnosis [21,22]. In a number of works, the use of quantum dots (QDs) was suggested as a means to increase the sensitivity of ICA [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%